2015
DOI: 10.1111/jonm.12332
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review: barriers to hourly rounding

Abstract: Leaders can utilise this information to analyse and create successful options to overcome these barriers before, during and after the implementation process. Further studies are needed to identify targeted strategies to alleviate these barriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 17 publications
4
21
0
Order By: Relevance
“…A list of potential 'backdrops' believed by authors to influence IR and a list of potential outcomes reported to arise from it were, however, identified and are highlighted in Appendices 1 and 2. The findings of this synthesis echo those of a systematic review of the barriers to effective implementation and sustainment of IR on medical and surgical wards, 62 as well as identifying additional barriers. In Table 3, the theories by which IR may work are made explicit, and CMO configurations that are to be tested and refined in later phases of the study are summarised.…”
Section: Box 3 the Cmo Configuration Associated With The Absence Of Tsupporting
confidence: 54%
“…A list of potential 'backdrops' believed by authors to influence IR and a list of potential outcomes reported to arise from it were, however, identified and are highlighted in Appendices 1 and 2. The findings of this synthesis echo those of a systematic review of the barriers to effective implementation and sustainment of IR on medical and surgical wards, 62 as well as identifying additional barriers. In Table 3, the theories by which IR may work are made explicit, and CMO configurations that are to be tested and refined in later phases of the study are summarised.…”
Section: Box 3 the Cmo Configuration Associated With The Absence Of Tsupporting
confidence: 54%
“…• However, a number of barriers to effective hourly rounding have been reported. A systematic review [7] reported that competing tasks and priorities, limited time, and the workload in medical-surgical units were considered to interfere with consistent hourly rounding. Further, staff thought that the documentation associated with rounding was irrelevant and a waste of time.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of intentional rounding (IR) in acute healthcare settings has recently gained prominence as an intervention to improve patients’ safety, outcomes and satisfaction (Fitzsimons, Bartley, & Cornwell, ; Flowers et al., ; Toole, Meluskey, & Hall, ). IR is defined as “regular checks of individual patients carried out by health professionals at set intervals to proactively enquire into care they may need” (Harrington et al., , p. 523).…”
Section: Introductionmentioning
confidence: 99%